Homebound Patient and Caregiver Perceptions of Quality of Care in Home‐Based Primary Care: A Qualitative Study. Issue 8 (7th July 2016) - Shafir, Adi; Garrigues, Sarah K.; Schenker, Yael; Leff, Bruce; Neil, Jessica; Ritchie, Christine
Abstract : Objectives: To assess patient and caregiver perceptions of what constitutes quality care in home‐based primary care (HBPC). Design: Cross‐sectional qualitative design; semistructured interview study. Setting: Academic home‐based primary care program. Participants: Homebound patients (n = 13) and 10 caregivers (n = 10) receiving HBPC. Measurements: Semistructured interviews explored experiences with a HBPC program and perceptions of quality care. Interviews were audio‐recorded and transcribed. Qualitative content analysis was performed to identify major themes. Results: Five major themes emerged related to participant perceptions of quality care: access, affordability, competency, care coordination, goal attainment. Participants felt that reliable, consistent access provided "peace of mind" and reduced hospital and emergency department use. Insurance coverage of program costs and coordinated care provided by an interdisciplinary team were positively regarded. Interpersonal skills and technical abilities of providers influenced patient perception of provider competency. Assessing and helping patients attain care goals contributed to a perception of quality care. Conclusion: Patients and caregivers associate high‐quality HBPC with around‐the‐clock access to affordable interdisciplinary providers with strong interpersonal skills and technical competency. These results expand on prior research and are concordant with HBPC goals of around‐the‐clock access to multidisciplinary teams with the goals of reduced emergency department and hospital use. HBPC programs should be structured to optimize access, affordability, coordinated care, and goal ascertainment and alignment. Quality indicators should be created and validated with these patient and caregiver views of care quality in mind.